Pengaruh Metode Pembelajaran Problem Solving terhadap Hasil Belajar Matematika Ditinjau dari Kemandirian Belajar - Huri Suhendri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
The purpose of this study is analyzing the interaction effect of teaching methods of problem solving and independent learning on learning outcomes of mathematics. The research was conducted at Charity SDIT Honor, Depok, West Java class V students with affordable population by 46 students. While the number of samples in the study consisting of 40 students from class VA (experimental class) as many as 20 students and class VB (grade control) as many as 20 students. The research method used is a truly experimental (true experimental) with hypothesis testing techniques used in this study is two lanes with a factorial ANOVA 2 x 2. Test requirements of data analysis is the test of normality and homogeneity tests. The test results showed that all groups of data are normally distributed and homogeneous. Hypothesis testing results showed no interaction effect of learning methods of problem solving and independent learning on learning outcomes of mathematics. Based on these results, it is necessary that the teacher in the learning of mathematics applying problem solving and learning methods work to improve student learning independence.